2010
DOI: 10.1007/978-3-642-13681-8_31
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance of a Noise Reduction Algorithm by Switching the Analysis Filter Bank

Abstract: A new approach for preservation of transient parts of speech in a noise reduction system is proposed in this paper. Transient components of speech such as vowel onset and beginning of some consonants such as stop sounds are important parts for intelligibility of speech. These components are usually attenuated by noise reduction algorithms due to the low temporal resolution of block-based noise reduction techniques. A method is proposed to detect the transient component of speech, followed by dynamic switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A number of adaptive time-frequency (TF) resolution schemes have been suggested, see for instance [8], [9] and the references therein. Also, it has been shown that adapting the TF resolution can lead to improvements in noise reduction [10], [11]. Common for these approaches is that they are not suitable for low delay implementations since they require longer time windows to determine the TF resolution and/or that they have a high computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of adaptive time-frequency (TF) resolution schemes have been suggested, see for instance [8], [9] and the references therein. Also, it has been shown that adapting the TF resolution can lead to improvements in noise reduction [10], [11]. Common for these approaches is that they are not suitable for low delay implementations since they require longer time windows to determine the TF resolution and/or that they have a high computational complexity.…”
Section: Introductionmentioning
confidence: 99%